RESPON PENGGUNA LULUSAN JURUSAN PENDIDIKAN AGAMA ISLAM FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR: Studi Kasus Pada Kota Makassar - ., Usman (Inspiratif Pendidikan, 2017)
This paper is the result of the author's research which is compiled into a journal with the main problem of how the user response is graduated from the Department of Islamic Religious Education of Faculty of Tarbiyah and Teacher Training UIN Alauddin in Makassar City in terms of professionalism, information, ability to communicate, teamwork, and ability to do self-development. Sources of data as respondents consist of elements of schools and madrassas in Makassar City who have PAI subject teachers or clumps of PAI subjects who have an undergraduate education background in the Department of PAI Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. School and madrasah in question amounted to 15 schools / madrasah with the number of teachers assessed by the principal / madrasah amounted to 40 people. The results showed that the attitude of professionalism of alumni of Islamic Education Department Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar included in very good category with value 3,66; attitudes of integrity (ethics and morals) are included in the excellent category with a score of 3.74; abilities in the language fall into either category with a value of 2.70; ability to use information technology in learning activities included in good category with value 3,32; communication ability included in very good category with value 3,70; team cooperation ability included in very good category with value 3,61; and ability to do self-development included in good category with value 3,49.